Proposed Localized Wind-Driven Rain Test Parameters for Building Envelopes in Metro Manila - Sadie, Homer; Diola, Nathaniel (Philippine Engineering Journal, 2020)
Abstract – Rainwater intrusions in building envelopes have been recognized as the primary source of material deterioration inside buildings. These occurrences are partially attributed to wind-driven rain (WDR) scenarios. Local testing procedures and parameters to assess systems of building envelopes against WDR and its contributing leakage have not yet been established. After adapting international methodologies, a set of testing parameters are calculated. Parameters are pairings of spray rates and static pressures associated with return period for Metro Manila. The flow rates range from 5.89-16.05 L/min m 2 , while the static pressure pairings range from 90 to 481 Pa for considered return periods of 2, 5, 10, 20 and 30 years. These calculated values are generally higher than the endorsed minimum from several ASTM standards and comparable to other testing parameters used in other countries. Therefore, the usage of preset WDR test parameters from the ASTM standards, might not reflect the expected climate event specific for Metro Manila.   Keywords – wind-driven rain, water leakage, static pressure, test parameters, Metro Manila